Modern and contemporary physics: content analysis of the high school physics books approved by the 2018 PNLD (Revista Contexto & Educação, 2023)
In this research, the results of an analysis carried out on didactic works approved in the National Textbook Program (PNLD) of 2018 for the discipline of Physics are presented. The objective is to evaluate how the contents of Modern and Contemporary Physics (FMC) are being presented in these materials, highlighting the main strengths and weaknesses of each work. The corpus of this research comprised three didactic works chosen by state public schools in São Luís - Maranhão. The applied methodology was guided by the qualitative approach and documentary typology. The results reveal that the didactic works analyzed can be considered good tools for the Physics Teaching process, although some works do not contain all the relevant FMC topics for scientific and citizen education of the student. It was evident that among the criteria investigated, interdisciplinarity was considered satisfactorily. It is necessary, however, that the authors and evaluators of textbooks, pay attention to the relevance of the contents of FMC so that they do not fail to enable the teacher to work on several critical aspects of the contents, not restricting them only to the scientific concept of Physics.
Keywords: Modern and Contemporary Physics. Textbook. High school.